STRATEGI PEMASARAN PRODUK WISATA PT. SONGA ALAM LESTARI PROBOLINGGO JAWA TIMUR - Ariyani, Desak Ratih Duwi; Sudiarta, I Nyoman; Suwena, I Ketut (Jurnal Analisis Pariwisata, 2021)
This journal aims to determine the marketing activities that have been done by PT. Songa Alam Lestari and develop strategies and marketing programs that can be implemented by the company. The technique data collection using observation, interview, questionnaires and documentary study. Sampling technique using Accidental sampling. Data analysis technique used qualitative descriptive analysis, Likert scale analysis and SWOT analysis approach. The results of the research are twelve strength indicators, three weakness indicators, eight opportunity indicators and two threat indicators. Marketing strategies that can be implemented by the company that is 1) More create and develop a quality product 2) provide more discounts for customers who have used the service Songadventure several times. Advice given is more active doing promotional activities by doing Ecommerce marketing activities, multiply the cooperation with tourism or individual travel business. Keywords:: Marketing Strategy, Tourism Product, Tourism